Charging the Future: Wireless Power for Electric Vehicles (International Journal of Food and Nutritional Sciences, 2023)
The better results of electric vehicles as compared to fuel vehicles is continuously leading to a growthin demand of EVs. Better quality in driving, less noise, more efficiency, less running cost and smoothoperation of EVs is dominating all the drawbacks users were facing in fuel vehicles.